Food Insulin Index: Implications for Type 2 Diabetes Mellitus - Jargin, Sergei V. (European Journal of Therapeutics, 2022)
The education of diabetic patients about their disease is an integral part of prevention, treatment and care (1). Realistic perceptions about nutrition are important for the control and prevention of complications (2). This letter questions the usefulness of the food insulin index (FII) concept for the management of type 2 diabetes mellitus (T2DM) with overweight. FII has been proposed to quantify postprandial insulin response to a food in comparison with an isoenergetic portion of a reference food such as white bread or glucose (3, 4).